PENERAPAN PEMBELAJARAN BERBASIS ETNOMATEMATIKA BERBANTUAN VBA FOR MICROSOFT EXCEL TERHADAP RESILIENSI SISWA SMP - Sari, Dewi Ratna; -, Linda; Fitriani, Nelly; Nurfauziah, Puji (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2019)
The purpose of this research is to see the resilience of students in classes that use mathematical learning etnomatematika based assisted VBA for Microsoft Excel. The method used is qualitative descriptive. The population in this study are all junior high school students. Sample was taken by purposive sampling that junior high school students in one school in West Bandung as many as 31 students. The instruments used are questionnaires mathematical resilience. The result obtained is equal to 39% of the students already have a good resilience. The conclusions that aided etnomatematika based learning VBA for Microsoft Excel supports resilience mathematics achievement of students. Based on this, a very good learning this kind to be developed.